Analisi Feasibility Analysis Of Tas Small To Medium Industrial Enterprises In Tanggulangin District, Sidoarjo Regency - Putri Putri Nadila Nindia Frisca (IHSA Institute, 2023)
Small and medium industries (IKM) have made a major contribution to national economic growth and societal welfare. The important role of the SME sector can be seen from the absorption of the workforce which reached 12.39 million people or contributed 66.25% of the total workforce in the industrial sector. The important role of the SME sector can be seen from the absorption of the workforce which reached 12.39 million people or contributed 66.25% of the total workforce in the industrial sector. SMEs were able to contribute to the growth of the non-oil and gas industry by 21.22%. This research uses a qualitative analysis method with primary data and secondary data. Data was collected through literature study, observation, interviews and documentation conducted on six bag business informants in Kedensari Village, Tanggulangin District, Sidoarjo Regency. Business feasibility analysis is determined using a cost and profit analysis formula. The formula used is analysis of the R/C ratio, B/C ratio, and ROI. Based on the results of research conducted on six bag entrepreneurs in Kedensari Village, Tanggulangin District, Sidoarjo Regency, analysis of the R/C ratio, B/C ratio, ROI shows results >1 which indicates that the business is feasible. This shows that the profit value obtained by bag entrepreneurs is more than the total costs and business capital incurred during bag production.